Sequential combination of gemtuzumab ozogamicin and standard chemotherapy in older patients with newly diagnosed acute myeloid leukemia: results of a randomized phase III trial by the EORTC and GIMEMA consortium (AML-17) - Amadori, Sergio; Ho, Anthony Dick (Journal of clinical oncology, 2013)
Purpose This randomized trial evaluated the efficacy and toxicity of sequential gemtuzumab ozogamicin (GO) and standard chemotherapy in older patients with newly diagnosed acute myeloid leukemia (AML). Patients and Methods Patients (n = 472) age 61 to 75 years were randomly assigned to induction chemotherapy with mitoxantrone, cytarabine, and etoposide preceded, or not, by a course of GO (6 mg/m2 on days 1 and 15). In remission, patients received two consolidation courses with or without GO (3 mg/m2 on day 0). The primary end point was overall survival (OS). Results The overall response rate was comparable between the two arms (GO, 45%; no GO, 49%), but induction and 60-day mortality rates were higher in the GO arm (17% v 12% and 22% v 18%, respectively). With median follow-up of 5.2 years, median OS was 7.1 months in the GO arm and 10 months in the no-GO arm (hazard ratio, 1.20; 95% CI, 0.99 to 1.45; P = .07). Other survival end points were similar in both arms. Grade 3 to 4 hematologic and liver toxicities were greater in the GO arm. Treatment with GO provided no benefit in any prognostic subgroup, with the possible exception of patients age < 70 years with secondary AML, but outcomes were significantly worse in the oldest age subgroup because of a higher risk of early mortality. Conclusion As used in this trial, the sequential combination of GO and standard chemotherapy provides no benefit for older patients with AML and is too toxic for those age ≥ 70 years.